2006
DOI: 10.1074/jbc.m506911200
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Olfactory Neurogenesis Requires HSF1, a Major Heat Shock Transcription Factor in Mice

Abstract: Heat shock transcription factors (HSFs) play roles not only in heat shock response but also in development of the reproductive organs, brain, and lens. Here, we analyzed sensory organs and found abnormalities of the olfactory epithelium in adult HSF1-null mice, which is developmentally related to the lens. The olfactory epithelium was normal until postnatal 3 weeks but was not maintained later than 4 weeks in HSF1-null mice. The olfactory epithelium was atrophied with increased cell death of olfactory sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
74
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 51 publications
8
74
0
Order By: Relevance
“…Furthermore, hsf1 À/À female mice exhibit complete infertility whereas male mice are fertile. In addition, hsf1 deficiency causes central nervous system defects (unpublished), neuronal defects (Takaki et al, 2006) and lack of spermatogenesis in conjunction with hsf2 deficiency (Wang et al, 2004). These defects are linked to Hsf1-mediated pathways regulating expression of diverse array of target genes including Hsps, growth factors and cytokines in the mutant mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hsf1 À/À female mice exhibit complete infertility whereas male mice are fertile. In addition, hsf1 deficiency causes central nervous system defects (unpublished), neuronal defects (Takaki et al, 2006) and lack of spermatogenesis in conjunction with hsf2 deficiency (Wang et al, 2004). These defects are linked to Hsf1-mediated pathways regulating expression of diverse array of target genes including Hsps, growth factors and cytokines in the mutant mice.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanisms of how HSFs act in these physiological processes are still unclear, genetic evidence shows that HSFs regulate constitutive gene expression in unstressed cells and tissues (27,28). Furthermore, it was revealed in sensory and immune cells that HSFs not only maintain protein homeostasis by regulating constitutive expression of Hsps, but are also involved in cell growth and differentiation by regulating expression of cytokines such as interleukin-6, fibroblast growth factors, and LIF (22,24,25). However, we do not know any client protein stabilized by Hsps that is under the control of HSFs in unstressed conditions.…”
mentioning
confidence: 99%
“…Inversely, HSF1 also regulates proapoptotic genes to decide on cell death or life in response to stress (12)(13)(14). In addition to the role in heat shock response, HSFs play critical functions in developmental processes such as gamatogenesis and neurogenesis (15)(16)(17)(18)(19)(20), in maintenance of the sensory organs (21)(22)(23)(24), and in immune response (25,26). Although the precise mechanisms of how HSFs act in these physiological processes are still unclear, genetic evidence shows that HSFs regulate constitutive gene expression in unstressed cells and tissues (27,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Homma et al (48) observed hallmarks of central nervous system disease, such as demyelination, astrogliosis and accumulation of ubiquitinated proteins in HSF1-deficient mice. Furthermore, previous studies with HSF1 KO animals have shown that HSF1 is involved in the development and maintenance of several organs, such as the heart (49), trachea (50), nose (50) and placenta (47). It has also been demonstrated that both HSF2 (51) and HSF4 (52) play critical roles in the neural functions or lens development by using HSF2-and HSF4-KO mice.…”
Section: Function Of Hsf1mentioning
confidence: 95%